Evaluating Training Programs in the Light of Effective Teaching Skills from the View Points of Educational and Specialization Supervision in Diyala Province as a Model (Journal of the College of Basic Education, 2022)
The paper is aiming at Evaluating Training Programs in the Light of Effective Teaching Skills from the View Points of Educational and Specialization Supervision in Diyala Province as a Model. The two researchers adopted the descriptive method (survey study). The sample of the study comprised of the simple sample (accidental) which consisted of (40) male and female, educational and specialization supervisors working in the Directorate of Educational Supervision in a total number of (16) educational supervisors and (24) specialization ones. To achieve the aim of the paper, and to answer its questions, the two researchers adopted an electronic form which consisted in its final form of (45) items distributed on (9) basic skills equally as of (5) sub-skills per each major skill, namely (mental priming, diversification of stimuli, teaching aids, motivation, explanation and interpretation, reinforcement, discussion, students' learning styles, closing). Furthermore, the validity and reliability of the tool were both verified as the reliability was (0.88) in terms of the repetition method, whereas it was (0.86) via internal consistency method using the Alpha Cronbach equation. The questionnaire was implemented on the research sample members, educational and specialization supervisors, through Google Drive platform starting from the 29th of May 2020. After data collection and statistical analysis using the Statistical Bag of Educational and Social Sciences (SPSS) along with weighted average equation and one sample Z-Test, the results indicated:1. There is no statistically significant difference between the ratios achieved in the nine effective teaching skills and the hypothetical ratio at the stake of (70%) among educational supervisors2. There is no statistically significant difference between the ratios achieved in the nine effective teaching skills and the hypothetical ratio at the stake of (70%) among specialization supervisors. In the light of the results, the two researchers came up with a number of conclusions, including: The effectiveness of training programs in enabling primary and secondary school teachers of effective teaching skills efficiently. They also recommended emphasizing the development of training programs as well as proposing a number of future titles for subsequent studies.